2019
DOI: 10.1111/jocn.15020
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an index system for qualitative evaluation of undergraduate nursing students innovative ability: A Delphi study

Abstract: Aim and objective To establish an index system for the evaluation of undergraduate nursing student innovation ability. Background An index system for evaluation of undergraduate nursing student innovation ability has not been established. Design A three‐round Delphi survey sought opinions from experts about the index system for evaluation of undergraduate nursing student innovation ability. Methods A Delphi survey was used for the study of 19 experts from nursing education, clinical nursing and health manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…Based on previous research, an expert consultation authority coe cient > 0.7 is considered to be reliable. An authority coe cient of 0.8 indicates even higher reliability of the experts' judgement [2,6]. In this study, the authority coe cient of the experts was 0.91 ± 0.07, which indicated that the experts' evaluation perspective are more experienced and reliable.…”
Section: Experts' Authoritymentioning
confidence: 56%
See 2 more Smart Citations
“…Based on previous research, an expert consultation authority coe cient > 0.7 is considered to be reliable. An authority coe cient of 0.8 indicates even higher reliability of the experts' judgement [2,6]. In this study, the authority coe cient of the experts was 0.91 ± 0.07, which indicated that the experts' evaluation perspective are more experienced and reliable.…”
Section: Experts' Authoritymentioning
confidence: 56%
“…Data were collected and calculated for stability of the consensus, experts' enthusiasm, experts' authority, and experts' agreement [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kendall's W test was used to confirm the consistency of the experts' answers to all the items (Fu et al, 2016). The authority coefficient (Cr) was used to measure the reliability and representation of the expert consultations, which was Cr = (Cs + Ca)/2, where Cs was the experts' familiarity with the items and Ca was the judgement criteria (Dai et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Two independent samples were used for EFA and CFA. According to Dai et al (2019), the sample size for EFA should be no less than 150, and for CFA should be more than 200. Considering the nonresponse deviation, the sample size should also be increased by 10% (Lyu et al, 2020).…”
Section: Samples and Settingmentioning
confidence: 99%